2010
DOI: 10.1590/s0103-84782010000600031
|View full text |Cite
|
Sign up to set email alerts
|

Growth retardants in wheat and its effect in physiological quality of seeds

Abstract: Plant lodging in wheat has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
3
0
4
Order By: Relevance
“…При этом важно, что сам ход физиологических процессов, определяющих продукционную способность обработанных растений, не должен претерпевать существенных изменений. Данные о влиянии ретардантов на физиологические функции растений противоречивы, однако большинство результатов свидетельствует, что ре гуляторы роста растений не оказывают отрицательного воздействия на фотосинтез, ограничивают чрезмерный расход воды и обеспечивают более благоприятный водный режим (Шаповал и др., 2010; Souza et al, 2010).…”
Section: факторы вызывающие полеганиеunclassified
“…При этом важно, что сам ход физиологических процессов, определяющих продукционную способность обработанных растений, не должен претерпевать существенных изменений. Данные о влиянии ретардантов на физиологические функции растений противоречивы, однако большинство результатов свидетельствует, что ре гуляторы роста растений не оказывают отрицательного воздействия на фотосинтез, ограничивают чрезмерный расход воды и обеспечивают более благоприятный водный режим (Шаповал и др., 2010; Souza et al, 2010).…”
Section: факторы вызывающие полеганиеunclassified
“…However, some research reports concluded that foliar application of chlormequat and trinexapacethyl did not affect the physiological quality of wheat seeds (SOUZA et al, 2010), most publications point to the decrease of protein content, gluten content and the falling number (CACAK-PIETRZAK et al, 2006) after application of growth retardants. The investigations showed a varying impact of retardants on the evaluated Table 3 -Influence of mix application growth regulators with adjuvants on thousand grain weight and grain yield of wheat.…”
Section: Grains/ear ---------------------------------------Experimentmentioning
confidence: 99%
“…The products aimed at preventing crop lodging of cereals are based on a number of active substances, including chlorocholine chloride, mepiquat chloride, paclobutrazoles, etephon, trinexapac-ethyl and prohexadione calcium. Their main role is to shorten and stiffen the stems, although in the light of today's research it has already been established that these substances, acting as growth and development regulators, allow for exploiting the yield potential more fully also in the absence of crop lodging (Matysiak 2006;Espindula et al 2009;de Souza et al 2010;Espindula et al 2011). The reduction of stem length as a result of using retardants is closely related to the reduction of gibberellin synthesis -this is how trinexapac-ethyl, chlormequat chloride, mepiquat chloride, paclobutrazol, prohexadione-calcium work -or to the increase of ethylene synthesis (ethephon).…”
Section: Introductionmentioning
confidence: 99%